A long and narrow pulmonary vein thrombus attached to the wall of a pulmonary vein - Hidekazu Takeuchi (International Journal of Cardiology: Heart & Vasculature, 2015)
Pulmonary vein thrombosis (PVT) is often not diagnosed because PVT has subtle symptoms and PVT is believed to be rare. The mechanism for the formation of PVT is unclear. In this case, I describe a small thrombus in a small branch of a pulmonary vein draining into a larger vein, the right lower pulmonary vein (RLPV). The patient was a 70-year-old male with angina pectoris, and he presented with chest pain. He had no symptoms of cerebral infarction. He previously had been treated with percutaneous coronary intervention and had four stents in the coronary arteries. A 64-slice multidetector computed tomography (64-MDCT) scan was performed to evaluation for in-stent restenosis. A thrombus in the RLPV was shown in axial and sagittal images as a defect in contrast enhancement, representing a small thrombus in a small branch of a pulmonary vein draining into the RLPV. The 64-MDCT scan depicted them well. The effects of PVT are unknown, and more studies are needed.